EFEKTIVITAS PENERIMAAN PAJAK PENGHASILAN FINAL (PPH-FINAL) DI SEKTOR UMKM PADA KPP NGAWI - Sulastri Andayani; Subagyo Subagyo; Wibowo Andoko (CAHAYA AKTIVA, 2018)
The government's effort in increasing its largest income is from taxation, especially in the sector of Micro SmallMedium Enterprises (MSMEs). Government Regulation (PP) No. 46 of 2013 is about taxation on the perpetrators of MSME of 1% of gross turnover or turnover not exceeding 4.8billion. The purpose of this study is to determine the effectiveness and development of final income tax revenue on the sector of SMEs in the Office of Primary Tax Service in Ngawi City. Methods of data collection in this study is by documentation and literature study. While the data analysis method used is descriptive analysis. The results of the discussion show that (1) the Final Income Tax on Tax Receipts in the Tax Office Primary of Ngawi City in 2015 has a good development even though it has not reached the target that has been determined. (2) For 2016, the development of final income tax on tax receipts KPP Ngawi also experienced a good development or rise and can be quite good, although also not yet able to reach the target specified. (3) The effectiveness of Final Income Tax on MSME sector in KPP PratamaNgawi in 2015 is effective even though it has not reached the good or very effective category, whereas in 2016 the effectiveness that happened can be said is high or quite effective compared to the year 2015. Key Word : Effectiveness of Final Income Tax Receipts in MSMEs Sector at KPP PratamaNgawi.